Anxiety, Depression and Functional Impairment among Health Care Workers during COVID-19 Pandemic: A Crosssectional Online Survey - Shrestha, R.; Khatri, B.; Adhikari, S.; Poudyal, P. (Kathmandu University Medical Journal, 2021)
Background COVID-19 is an infectious disease caused by a newly discovered coronavirus. The number of cases and dramatic loss of human life worldwide created psychological problems among general public, including health care workers. Objective To determine the burden of anxiety, depression, and functional impairment among health care workers in the early days of lockdown during the first wave of COVID-19 outbreak in Nepal. Method A hospital-based cross-sectional study was carried out among all the employees of Hospital for Children Eye ENT and Rehabilitation Services, Bhaktapur during the COVID-19 pandemic lockdown from April 3, 2020 to May 2, 2020 using an online questionnaire. The tools used were adopted from Nepali version of Hospital Anxiety and Depression scale (HADS) and Nepali version of WHO Disability Assessment Schedule (WHODAS 2.0). Result The mean age (SD) of the participants (n=86) was 32.53 (7.92) years. Male and female participants were equal in number. The point prevalence of anxiety and depression was 25.6% and 14.0%, respectively. Females had a higher prevalence of both anxiety (39.5% vs 11.6%, p < 0.01) and depression (18.6% vs 9.3%, p=0.351). Clinical and nonclinical staff both had a higher prevalence of both anxiety (31.0% and 20.5%, p=0.265) and depression (16.7% and 11.4%, p=0.478). The mean functional impairment score (WHODAS 2.0) among all participants and participants with anxiety and depression was 19.47 (95% CI: 18.13-20.80), 21.27 (95% CI: 18.08-24.46), and 19.92 (95% CI: 15.28- 24.56), respectively. Conclusion Anxiety and depression during the first lockdown due to COVID-19 pandemic were highly prevalent in clinical and non-clinical employees. Besides controlling the outbreak, special consideration should be given to mental health.